Efforts of Islamic Religious Education Teachers in Developing Learning Independence in Broken Home Students - Dewi Khusnul Khotimah; Sutiah Sutiah; Esa Nur Wahyuni (Sekolah Tinggi Agama Islam Sumatera Medan, 2025)
Family broken home has the potential to reduce gacor slot children's psychological, social, and academic aspects, including the important character of independent learning in educational achievement. This study highlights the urgency of a holistic approach to Islamic Education that encompasses cognitive, affective, and spiritual dimensions, especially in guiding students from broken homes. The objectives are to describe the learning independence gacor slot characteristics of students at SD Kartika Nawa Turen, analyze the role of Islamic education teachers in its development, and assess its impact on students' behavior and learning processes. This study employs a qualitative approach using the case study method. Data collection techniques include observation, interviews, and documentation, analyzed using the Miles and Huberman model. The results gacor slot indicate that students' learning independence is still low. Islamic Education teachers implement positive habit-forming strategies, modeling, emotional-spiritual approaches, and collaboration with parents. These strategies have proven effective in enhancing self-awareness, responsibility, and reducing students' dependence. This study makes an important contribution to the application of affective approaches in Islamic Education learning in challenging environments.